The emergence and transformation of Batkhela (Malakand) Bazaar: Ethnic entrepreneurship, social networks, and change in disadvantageous societies - Jan, Muhammad Ayub (International Food Policy Research Institute, 2014)
This study is an inquiry into the emergence and transformation of Batkhela bazaar in the North West of Pakistan. It investigates the emergence of the bazaar in the face of historical conditions that were characterized by social stratification and political exclusivity. It then probes the transformation of Batkhela bazaar and it’s functioning in the current socio-political conditions. We investigate the above processes with a focus on entrepreneurs of the bazaar. Particularly we examine their efforts in challenging historical conditions during the emergence of the Batkhela bazaar and their continuous endeavor to keep the bazaar functioning. The study also reflects on the social and political embeddedness of the entrepreneurial activities of the bazaar.